Moving-boundary problems for the time-fractional diffusion equation - Sabrina D. Roscani (Electronic Journal of Differential Equations, 2017)
We consider a one-dimensional moving-boundary problem for the time-fractional diffusion equation. The time-fractional derivative of order $α\in (0,1)$ is taken in the sense of Caputo. We study the asymptotic behaivor, as t tends to infinity, of a general solution by using a fractional weak maximum principle. Also, we give some particular exact solutions in terms of Wright functions.